Endogenous SO2 Controls Cell Apoptosis: The State-of-the-Art - Li, Yingying; Feng, Yingjun; Ye, Xiaoyun; Peng, Hanlin; Du, Jiantong; Yao, Xiaoli; Huang, Yaqian; Jin, Hongfang; Du, Junbao (Frontiers in Cell and Developmental Biology, 2021)
SO2, previously known as the product of industrial waste, has recently been proven to be a novel gasotransmitter in the cardiovascular system. It is endogenously produced from the metabolism pathway of sulfur-containing amino acids in mammalians. Endogenous SO2 acts as an important controller in the regulation of many biological processes including cardiovascular physiological and pathophysiological events. Recently, the studies on the regulatory effect of endogenous SO2 on cell apoptosis and its pathophysiological significance have attracted great attention. Endogenous SO2 can regulate the apoptosis of vascular smooth muscle cells, endothelial cells, cardiomyocytes, neuron, alveolar macrophages, polymorphonuclear neutrophils and retinal photoreceptor cells, which might be involved in the pathogenesis of hypertension, pulmonary hypertension, myocardial injury, brain injury, acute lung injury, and retinal disease. Therefore, in the present study, we described the current findings on how endogenous SO2 is generated and metabolized, and we summarized its regulatory effects on cell apoptosis, underlying mechanisms, and pathophysiological relevance.